Preparing for retirement: The pension arrangements and retirement expectations of those approaching state pension age in England - James Banks; Carl Emmerson; Zoë Oldfield (Institute for Fiscal Studies (IFS), 2005)
This paper provides a detailed analysis of individuals in households in England aged between 50 and the State Pension Age in terms of their private pension arrangements and current non-pension assets alongside their expectations of future economic circumstances. Our descriptive findings include that members of defined benefit pensions have higher average levels of current earnings than members of defined contribution pensions and that median expected private pension income in retirement is highest for current members of defined benefit schemes. We find that on average those who have, or have had, a private pension have greater non-pension wealth than those who have never had a private pension. In terms of expectations of the future we find that it is those who have the fewest assets who have the least attachment to the labour market and are far less likely to expect any inheritance. Hence we conclude that inequalities in different dimensions of retirement resources tend to reinforce themselves as opposed to offset each other. This working paper was updated in October 2005 to take account of revised housing wealth numbers. Appendices containing additional tables can be downloaded here: Section 2 pdf file [138 KB]; Sections 3 pdf file [119 KB]; Section 4 pdf file [179 KB]
Keywords: 330; Altersgrenze; Gesetzliche Rentenversicherung; Betriebliche Altersversorgung; Private Rentenversicherung; Großbritannien